1998
DOI: 10.1055/s-2007-1007167
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Liver in Interorgan Homeostasis of Glutathione and Cyst(e)ine

Abstract: The most widely recognized function of reduced glutathione (GSH) is its defense against toxic compounds, whether exogenous, such as electophilic xenobiotics, or endogenous, such as reactive oxygen species, generated during normal oxidative metabolism and/or stress. However another no less significant role of GSH-namely its function as a reservoir and vehicle for packaging and transport of cyst(e)ine-has been receiving increasing attention. Because GSH is relatively more auto-oxidation resistant and stable than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
131
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 2 publications
7
131
0
2
Order By: Relevance
“…[13] In addition to serving as a strate for glutathione related enzymes, GSH acts as a free radical scavenger, a generator of a α-tocopherol and plays an important role in the maintenance of protein sulfhydryl groups. [14] In the present study, the levels of GSH were decreased significantly in high fat diet ingestion indicating the oxidative stress. GPx has a well-established role in protecting cells against oxidative injury.…”
Section: Resultssupporting
confidence: 54%
“…[13] In addition to serving as a strate for glutathione related enzymes, GSH acts as a free radical scavenger, a generator of a α-tocopherol and plays an important role in the maintenance of protein sulfhydryl groups. [14] In the present study, the levels of GSH were decreased significantly in high fat diet ingestion indicating the oxidative stress. GPx has a well-established role in protecting cells against oxidative injury.…”
Section: Resultssupporting
confidence: 54%
“…16 There are a number of pitfalls in measurement but 3 modern methods are in fairly close agreement that concentrations of plasma GSH are about 20 µmol/L 16 and that hepatic vein concentrations are higher at about 30 µmol/L. 16 This is within the range of concentration for which the authors have demonstrated inhibitory activity of GSH for MMP9. Using in situ microdialysis, Yang et al measured basal extracellular GSH concentrations in the livers of anesthetized rats.…”
Section: Discussionmentioning
confidence: 94%
“…18 However, the exact role of extracellular glutathione remains poorly understood. 16 Glutathione is also a heavy metal-binding ligand, binding to mercury, copper, zinc, and other metals of biological importance, via the sulfhydryl group of the cysteine moiety. 19 As such, it is one of a group of thiols, such as N-acetylcysteine, dithioerythritol, and 2-mercaptoethanol that have been used to inhibit metalloproteinases in a variety of experimental situations.…”
Section: Discussionmentioning
confidence: 99%
“…Transport of these amino acids is accomplished by well-characterized amino acid transporters (13,14). More recently, distinct transport systems for GSH have been described on the canalicular and sinusoidal membranes of rat and human liver, and analysis of cell lines and tissues suggests that a transport mechanism also exists on certain other cell types (15)(16)(17)(18).…”
mentioning
confidence: 99%